Applied brocade in Spain - Ainhoa Rodríguez-López; Fernando Bazeta Gobantes (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The lack of thorough studies of the significant number of examples of applied brocade found in the last two decades in Spain, originated in 2009 a European PhD thesis with Honours. This investigation presents an analysis and classification of the patterns, making procedures and combinations of materials of the applied brocades of the wooden altarpieces of the Basque province of Gipuzkoa, Northern Spain. Further studies have focused on the use of other analytical techniques that have completed the previous results and more recently, are being examined patterns of applied brocades belonging to the altarpieces sited in the other two provinces of the Basque Country.